CRYPTOGRAPHIC ANALYSIS OF THE CODE STRUCTURES OF HERMITE CURVE FOR COMPLIANCE WITH THE REQUIREMENTS OF INFORMATION SECURITY SYSTEMS - V. V. Pankova; S. B. Salomatin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Building security systems based on the algebraic-geometric codes is possible with the use of various algebraic structures with cryptographic security. This paper investigates the properties of the code sequences, built on the Hermite curve in the field GF(16), their testing on the subject of the requirements for cryptographic transformations was conducted. Cryptographic analysis is performed using spectral transformations. Encrypted sequences quality metrics such as nonlinearity, balance, linear complexity are evaluated.